2022
DOI: 10.1186/s12986-022-00679-z
|View full text |Cite
|
Sign up to set email alerts
|

Absolute quantitative lipidomics reveals lipids profiling in liver of mice with early-stage alcoholic liver disease

Abstract: Background Alcoholic liver disease (ALD) is one of the most prevalent chronic liver disease worldwide. Alcohol-induced alterations in hepatic lipids play an important role in ALD develpoment and progression. The present study aimed to thoroughly describe the changes of lipid profiling in liver of mice with early-stage alcoholic liver disease. Methods C57BL/6J male mice aged 7-week were randomized into alcohol-fed (AF) group and pair-fed control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…TG and TC are important indicators of fat accumulation by alcohol consumption in liver injury [43]. Therefore, we confirmed the effect of the ESF administration on alcoholderived TG and TC levels.…”
Section: Effects Of Esf On Triacylglycerol (Tg) and Total Cholesterol...supporting
confidence: 78%
“…TG and TC are important indicators of fat accumulation by alcohol consumption in liver injury [43]. Therefore, we confirmed the effect of the ESF administration on alcoholderived TG and TC levels.…”
Section: Effects Of Esf On Triacylglycerol (Tg) and Total Cholesterol...supporting
confidence: 78%
“…For example, some studies reported that serum markers such as lipidomic markers, carbohydrate-deficient transferrin, or gamma-glutamyl transferase levels were of help. [26][27][28] However, they are not as widely available in the clinical setting, nor as understood, compared with performing and reading an MRI study. Indeed, our methods may even be incorporated into a scoring system that combines multiple modalities (e.g.…”
Section: Discussionmentioning
confidence: 99%